An analysis of ambulance re-contacts after non-conveyance: a retrospective cohort study in the Netherlands - Susanne E. de Loor; Tessa Verheij; Thomas Karol; Franciscus G. M. H. M. Cuppen; Frits van Dijk; Femke Goldstein; Joyce Janssen; Remco H. A. Ebben (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Non-conveyance is an increasing part of ambulance care and has to be safe. One of the indicators to measure safety is an ambulance re-contact within 72 h. However, solely measuring the percentage of re-contacts has limited validity as it lacks insight in actual reasons of an ambulance re-contact. Therefore, the aim of our study was to analyze the incidence, reasons and outcomes of ambulance re-contacts within 72 h after non-conveyance. Methods We conducted a one year (2022) retrospective study in one EMS region in the Netherlands. Medical records of all non-conveyance runs with a re-contact were analyzed using a framework to categorize re-contact reasons in illness-related, patient-related, professional-related, and unrelated. Re-contact outcomes were measured in terms of (non-)conveyance and mortality. Results 585/13.879 (4.2%) non-conveyance runs had a re-contact within 72 h. 547/585 (93.5%) re-contacts could be categorized with the framework. Re-contacts were related to the illness (n = 267, 48.8%), the patient (n = 130, 23.8%), the professional (n = 106, 19.4%) and unrelated (n = 44, 8.0%). Four subreasons accounted for 68.5% of reasons for re-contacts: progression of disease (19.4%), recurrent disease process/exacerbation (18.6%), reassessment and ambulance request by another medical professional (15.9%), and psychiatric disorder and/or substance abuse (14.6%). 403/547 (73.7%) patients with a re-contact were conveyed to the hospital. Mortality rate for patients with a re-contact was 0.5%. Conclusions Re-contact incidence after non-conveyance is relatively low, with a very small part of re-contacts related to ambulance care professionals making errors in diagnosis or treatment. Combined with low re-contact mortality, this indicates safe non-conveyance decisions. Re-contacts as quality indicator cover a variety of reasons, with almost half of the re-contacts being related to illness. Four subcategories accounted for the majority of all reasons for re-contacts: progression of disease, recurrent disease process/exacerbation, reassessment and ambulance request by another medical professional, and psychiatric disorder and/or substance abuse. Three-quarters of the patients were conveyed, although more re-contacts due to patient related reasons ended in non-conveyance again.